Determinantes econômicos e institucionais dos fluxos de investimento direto externo: evidência empírica para países desenvolvidos e em desenvolvimento - Lima, Lucas Damascena de (2024)
This study investigates Foreign Direct Investment’s (FDI) institutional and economic determinants in a group of 159 developed and developing countries, between 1971 and 2020. It is seek to provide holistic vision of variables that are significantly to FDI location decisions, with particular emphasis in role of institutional quality. From a panel data, the estimates are effectuated by GMM-system estimator. The results show that FDI are related with economic stability in developed countries, while in developing countries are related with market seeking strategies. Regarding institutional quality, this exhibit statistical significantly only developed countries, not show statistical in developing countries. Additionally, interactions between periods and institutions were performed. The results show that institutional quality was more important in 2001 and 2020 in developed countries. In developing countries, the institutional quality was important in 1991 and 2010, and, in 2011 and 2020, was negative associated with FDI inflows.